Linguistic superdiversity in urban areas : research approaches - Duarte, Joana; Gogolin, Ingrid (Hamburg studies on linguistic diversity ;, 2013)
Globalization poses challenges to sociolinguistics. The main challenge is to come to terms with the phenomenology of sociolinguistic globalization. This phenomenology touches four domains: proper globalization effects on language, the effect of globalization on migration patterns and immigrant communities, the effect of globalization, notably of the spread of English as a global language, on language hierarchies, and the domain of remote communities that have serious doubts regarding their possibilities of successfully participating in the globalization process. The sociolinguistics of globali.